Choledochoduodenostomy in the Management of Common Duct Stones or Associated Pathology – An Obsolete Method?. Issue 1 (1996) - de Almeida, António Castro Mendes; dos Santos, Noel Medina; Aldeia, Fernando José
Abstract : Choledochoduodenostomy (CDD) has been reported as a more effective treatment of CBD stones than T-tube drainage but it is regarded as a last resort or obsolete therapeutic method due to fears of higher mobidity, cholangitis, "sump" syndrome and liver dysfunction. We aimed to assess the aforementioned issues analyzing prospectively our experience from 1976 through Dec.92. Methods : CDD was performed in 89 females and 36 males, aged 60.2±8.7 years, 26 during repeat surgery. Duct stones were the indication in 94, Sphincter of oddi (SO) dysfunction in 23 and obstructive pancreatitis nodule in 8. Peroperative liver biopsies were obtained in 44 patients. The "follow-up" schedule (> 2.5 years in 110) included clinical interview and LFT's on an yearly basis. Ultra sound (USG) was obtained every one or two years. ERC was done in 10 symptomatic patients and in 25 others for protocul purposes. Liver biopsies were taken four to nine years post surgery in 11 patients-five at relaparotomy for non-biliary causes and six percutaneously by fine needle. Ductal mucosa biopsy could safely be performed in one patient 10 years after surgery. The long-term results were classified as excellent, good, fair or poor . Poor meant the need for further invasive therapy (resurgery or EST). Results : There were two operative deaths (1.6%). The long-term results (123 survivors) were considered excellent in 89, good in 22, fair in 9 and poor in three. Three patients died from unrelated causes and eight others ceased the "follow-up" evaluation three to five years post surgery. All of them were considered as having excellent or good results. A widely patent anastomosis of approximately 20 mms without mucosal inflammatory changes was documented in every patient assessed via ERC. food "debris" was detected within the distal duct of four patients yet it was easily flushed through the stoma. Normal tissue patterns were observed in all long-term liver biopsies. Likewise the ductal mucosa biopsy failed to reveal any acute or chronic inflammatory changes. Conclusions: 1) CDD is ahighly effective short and long-term treatment of CBD lithiasis.2) It does not lead to bacterial or "chemical" cholangitis, to "sump" syndrome or to hepatic dysfunction, provided a wide anastomosis is accomplished.3) CDD should only be considered as obsolete after extensive, long-term, prospective, randomized assessments of laparoscopic or combined laparoendoscopic approaches have been shown to be as effective as or superior to CDD.